CHARACTERIZATION OF RUBBER-MODIFIED POLYPROPYLENE - Nuri Astrini; E. L. Bedia; A. Sudarisrman (Research Center for Chemistry - LIPI, 1994)
Blending of 10, 20, 30, 40, and 50% ethylene-propylene random copolymer known as EPM with polypropylene (PP) was conducted and the blends were characterized using wide-angle x-ray scattering (WAXS), differential scanning calorimetry (DSC), scanning electron microscope (SEM), Tensile and Impact tester. As shown in WAXS diffractograms, PP retains its crystalline structure when blended with EPM. DSC analysis suggests that the polymer blend consists of two phase systems, one crystalline and one amorphous. Morphological observation of the polymer blend using SEM shows that the EPA-f globular structure cavitates the PP matrix which further indicates that the polymer blend is only partially compatible. As EPM increases, the tensile yield stress, stress-strain curve and modulus of elasticity decrease. Impact strength on the other hand, increases and showed remarkable effect at 30% EPM - 70% PP.